2022
DOI: 10.1093/jn/nxab401
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat Western Diet Attenuates Intestinal Changes in Mice with DSS-Induced Low-Grade Inflammation

Abstract: Background A Western diet (WD) is associated with increased inflammation in the large intestine, which is often ascribed to the high dietary fat content. Intestinal inflammation in rodents can be induced by oral administration of dextran sulfate sodium (DSS). However, most studies investigating effects of WD and DSS have not used appropriate low-fat diets as control. Objective To compare the effects of a WD with those of a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…This study also showed that the gut microbiota of mice fed with high-fat diets showed a higher Shannon index as compared to that of the mice fed with low-fat diets. Although it has been reported that the decreased bacterial richness can be considered a hallmark of the effects of a high-fat diet on the composition of gut microbiota in both humans and mice ( 44 ), more recent research conducted a study on the DSS-induced colitis mouse model (same as this study) and demonstrated a higher α-diversity (Shannon index) in the gut microbiota of mice fed with high-fat diet as compared to those fed with a low-fat diet ( 45 ). These seemingly contradictory conclusions suggested that the relationship between dietary factors and gut microbiota was highly complex and changeable, thereby requiring further investigations.…”
Section: Discussionmentioning
confidence: 96%
“…This study also showed that the gut microbiota of mice fed with high-fat diets showed a higher Shannon index as compared to that of the mice fed with low-fat diets. Although it has been reported that the decreased bacterial richness can be considered a hallmark of the effects of a high-fat diet on the composition of gut microbiota in both humans and mice ( 44 ), more recent research conducted a study on the DSS-induced colitis mouse model (same as this study) and demonstrated a higher α-diversity (Shannon index) in the gut microbiota of mice fed with high-fat diet as compared to those fed with a low-fat diet ( 45 ). These seemingly contradictory conclusions suggested that the relationship between dietary factors and gut microbiota was highly complex and changeable, thereby requiring further investigations.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study we examined the effect of a WD supplemented with two different fractions from faba beans in mice treated with 1% DSS for six days. Contrary to commonly used 2–5% DSS concentration for inducing colitis, we used 1% DSS to cause an irritation of the colon ideally mimicking a mild colitis phenotype consistent with low-grade colonic inflammation [ 46 48 ]. DSS treatments were combined with a commonly assumed unhealthy WD rich in fat and sucrose and low in dietary fibers, which may create an additional stress to the intestine [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…ideally mimicking a mild colitis phenotype consistent with low-grade colonic inflammation [46][47][48]. DSS treatments were combined with a commonly assumed unhealthy WD rich in fat and sucrose and low in dietary fibers, which may create an additional stress to the intestine [49].…”
Section: Plos Onementioning
confidence: 99%
“…Based on hospitalization diagnosis, IBD patients have a high body mass index because of high-fat diet (HFD) consumption, which exhibits deleterious effects [42]. The effect of liver disease on IBD progression is still unclear because a few dilemmas still support the theory that HFD intake damages the liver and exacerbates IBD, while others believe that HFD deleteriously affects the liver only and protects the intestine from its progression to IBD [43]. This review aims to summarize the molecular basis as to how dietary lipids intake acts as a dual sword in the case of IBD.…”
Section: Association Of Metabolic Disorder and Ibdmentioning
confidence: 99%
“…Experimentally, animal models fed with highfat diets have been systematically studied, and scientific evidence shows that consumption of a Western diet, which is high in fat, is directly linked to increased inflammation in the large intestine. Recent experimental studies have shown that mice fed a Western diet were protected from colonic inflammation compared to those fed a normal diet [43]. However, whether fat consumption triggers defensive cascades against DSS-induced inflammatory pathways or impedes the well-known DSS-induced colitis remains unclear.…”
Section: The Effects Of Fats On Ibdmentioning
confidence: 99%